Can green finance policies accurately promote corporate environmental investment?—a comprehensive evaluation from multiple aspects - Zhu, Ruoyan; Wang, Yuan; Li, Ruiling (Frontiers in Environmental Science, 2024)
The 28th United Nations Climate Change Conference, held in the United Arab Emirates at the end of November 2023, stated that climate action cannot be delayed and the financing and investment situation for adapting to climate change needs a qualitative leap. Vigorously developing green finance is one of the important ways to achieve this goal. The core question of this paper is: Can green finance policies promote enterprises' environmental investment? This article uses the formal implementation of the "Green Credit Guidelines" in 2012 as a quasi-natural experiment, bases on the micro data of A-share listed companies from 2004 to 2020, and adopts the difference-indifferences propensity score matching method (PSM-DID) to explore the role of green credit policy in guiding corporate environmental protection investment from multiple dimensions. The research shows that the implementation of the "Green Credit Guidelines" has promoted corporate environmental protection investment to a certain extent, and the conclusion still holds after a series of robustness tests. Heterogeneity tests found that the impact of green credit policy on corporate environmental protection investment varies significantly among different ownership enterprises and enterprises in different regions.Further research shows that the Green Credit Guidelines are regulated by macro and meso factors. From the perspective of mechanism, this paper finds out the mechanism of promoting enterprises' environmental protection investment at the micro level. At the macro level, economic policy uncertainty and monetary policy tightening affect the degree of corporate environmental protection investment. At the meso level, the government's attention to environmental protection determines the behavior of local enterprises, which in turn affects the attitude of enterprises towards environmental protection investment activities. At the micro level, the implementation of green credit on the one hand exacerbates the problem of corporate financing constraints, making companies have incentives to invest in environmental protection to alleviate this problem. On the other hand, it will also promote changes in innovation and capital factors in enterprises, directly increasing corporate environmental protection investment. This paper is helpful for the theoretical circle and management departments, so as to provide reference for the government to issue relevant policies.